Impact of Ginkgo biloba drug interactions on bleeding risk and coagulation profiles: A comprehensive analysis - Ngo Thi Quynh Mai; Nguyen Viet Hieu; Tran Thi Ngan; Tran Van Anh; Pham Van Linh; Nguyen Thi Thu Phuong (PLoS ONE, 2025)
This retrospective observational study was conducted to investigate the prevalence and clinical implications of drug interactions involving Ginkgo biloba extract on bleeding risk and coagulation profiles. Our analysis utilized data from patients admitted to Hai Phong International Hospital between January 2022 and December 2023. Inclusion criteria consisted of patients aged 18 years and above, those prescribed Ginkgo biloba extract alone or in combination with other medications, and the availability of complete medical records, including medication history, laboratory tests, and clinical outcomes. Out of 2,647 prescriptions meeting the inclusion criteria, 342 exhibited drug interactions with a prevalence rate of 12.94%. Notably, Ginkgo biloba extract frequent interacts with antiplatelets, anticoagulants, and nonsteroidal anti-inflammatory drugs, with Clopidogrel and Aspirin exhibiting the highest prevalence rates of 2.61% each. However, interactions with anticoagulants including direct oral anticoagulants and acenocoumarol, were not statistically significant in our analysis. Omeprazole was a frequently interacting drug (2.34%) of mild severity. Among the 747 patients analyzed for bleeding disorders, 31 (4.15%) exhibited bleeding symptoms. Correlation analysis indicated a strong association between clinical bleeding and abnormal coagulation results (OR, 1.75; p <  0.001). Moreover, significant correlations were found between Ginkgo biloba extract drug interactions and the bleeding risk (OR: 1.08, p <  0.001) and abnormal coagulation (OR: 1.49, p <  0.001). The severity of Ginkgo biloba extract drug interactions did not correlate with bleeding risk (OR: 1.01, p =  0.767) but influenced abnormal coagulation test results (OR: 0.813, p =  0.019). Specific medications, including clopidogrel, aspirin, celecoxib, loxoprofen, nifedipine, and omeprazole, were significantly associated with the risk of bleeding and abnormal coagulation (p <  0.05). Interactions with ticagrelor, etoricoxib, insulin, omeprazole, and domperidone were associated with abnormal coagulation tests without affecting the reported bleeding. These findings underscore the critical need of evaluating potential interactions involving Ginkgo biloba extract drug interactions in clinical pratice, particularly when assessing bleeding risk and managing coagulation.